The hide-and-seek effect of pulsed-flows in a potamodromous cyprinid fish - Renan Leite; Maria João Costa; Daniel Mameri; Fernando Afonso; António Pinheiro; José Maria Santos; Isabel Boavida (Hydrobiologia, 2024)
The artificial pulsed-flows impact associated with hydropower production on the downstream biological and physical processes has been extensively addressed, showing that it may cause fish drift while changing fish habitat selection toward lower water velocity patches, acting as refuge areas. We aimed to evaluate the attraction efficiency of two flow-refuges differing in their approaching angles, for Luciobarbus bocagei at an indoor experimental flume. We tested two flow-refuge insertion angles (45° and 70°), and two flow events (base 7 L/s and pulsed-flow 60 L/s) for each. To analyze flow-refuge efficiency, we quantified fish individual and group patterns, flow-refuge use, and permanence time, while measuring glucose and lactate responses. The results showed that the individual frequency of use during simulated pulsed-flow was higher, especially on the 45° flow-refuge. The simulated pulsed-flow condition did not disrupt group behavior for both approaching angles. Glucose and lactate analysis did not trigger physiological responses in the tested trials. The 45° flow-refuge was used more often than the 70°. The narrowing of the channel caused by the 45° flow-refuge, and the consequent higher flow homogeneity increased the attractiveness of the flow-refuge. Therefore, the flow-refuge insertion angle should be a decisive criterion in the construction and installation of flow-refuges for cyprinids, and be considered a potential indirect mitigation measure.